The effect of lutein on the oxidation of egg yolk phospholipids in a liposome model - Xiaoying Yang; Jinshan Xiao; Peng Wan; Jie Liu; Haitao Mo; De-Wei Chen (Food Chemistry: X, 2023)
Egg yolk phospholipids (PLs) extracted by organic solvent are prone to oxidation, while they are quite stable in egg yolk. This study was to verify the decisive role of lutein (naturally present in egg yolk) on the oxidative stability of PLs by constructing liposome. The liposome samples were heated at 100 °C for 10 min, and then the oxidation products of the liposome samples were analyzed by 1H NMR and GC–MS. The results showed that the concentrations of most of the oxidation products in the PLs-liposomes sample were significantly higher than those in the PLs&lutein-liposomes sample. Therefore, lutein could protect egg yolk PLs from oxidation, thus inhibiting the formation of lipid-derived volatile compounds. As those lipid-derived volatile compounds are the key fatty note odorants, this study has confirmed that the removal of lutein is the determining factor in using egg yolk PLs as an ideal precursor of fatty note odorants.